Factors affecting the implementation of inclusive education policy: A case study in one province in South Africa - Stofile, Sindiswa Yvonne (University of the Western Cape, 2014)
Philosophiae Doctor - PhD === The main aim of this study was to understand the factors that facilitate or constrain the implementation of inclusive education in the South African context. These factors were explored through a qualitative case study. A documentary analysis, as well as unstructured and semi-structured interviews was used to collect the data within die context of the research aims, questions, and a framework of categories, drawn from relevant literature, was used to analyse the data. The first major finding of this study was that the implementation of inclusive education policy in South Africa has been facilitated by the school communities' beliefs, values and norms relating to the inclusion of learners with disabilities. The second major finding of this study is that the designers of the inclusive education policy underestimated the deep-seated socio-economic factors that inhibit effective learning in certain contexts. Poverty was identified as a major constraining factor in the study, followed by the complexities of the National Curriculum Statement, a lack of capacity to implement the policy, lack of support for policy implementation, and the limitations of the Education White Paper 6 itself. Given the facilitating and constraining factors emerging from this study, the recommendations made have been based on the assumption that the implementation of inclusive education policy is a worthwhile endeavour. === South Africa